2009
DOI: 10.1590/s1517-83822009000100015
|View full text |Cite
|
Sign up to set email alerts
|

Yeast communities in two Atlantic rain Forest fragments in Southeast Brazil

Abstract: We studied the yeast communities associated with fruits, mushrooms, tree exudates, and flies of the genus Drosophila, in two Atlantic Rain Forest fragments in state of Minas Gerais, Brazil. A total of 456 samples were collected from Rio Doce State Park and 142 from Ecological Station of Universidade Federal de Minas Gerais. From these samples, 608 yeast isolates were obtained, belonging to 71 different species. Among the yeasts isolated from Rio Doce State Park, 17 isolates were recovered from fruits, 12 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The soil yeast species composition differed along the altitude gradient in the Brazilian forest domain. Basidiomycetous yeasts were found more often than ascomycetes in the studied soils, which is in agreement with previous reports on yeast species from forest soils (Sláviková and Vadkertiová, 2000;Stringini et al, 2008;Pimenta et al, 2009;Yurkov et al, 2012a;Mestre et al, 2014;Moreira and Vale, 2018). It has been suggested that basidiomycetous yeasts may be dominant in forest soils due to strategies and adaptations such as the production of polysaccharide capsules and stronger ability to use a wide range of carbon sources, including complex compounds (Vishniac, 2006;Connell et al, 2008;Yurkov 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The soil yeast species composition differed along the altitude gradient in the Brazilian forest domain. Basidiomycetous yeasts were found more often than ascomycetes in the studied soils, which is in agreement with previous reports on yeast species from forest soils (Sláviková and Vadkertiová, 2000;Stringini et al, 2008;Pimenta et al, 2009;Yurkov et al, 2012a;Mestre et al, 2014;Moreira and Vale, 2018). It has been suggested that basidiomycetous yeasts may be dominant in forest soils due to strategies and adaptations such as the production of polysaccharide capsules and stronger ability to use a wide range of carbon sources, including complex compounds (Vishniac, 2006;Connell et al, 2008;Yurkov 2018).…”
Section: Discussionsupporting
confidence: 91%
“…H. uvarum and S. cerevisiae have been already isolated from fruits and tree bark, respectively, in Amazonian and Atlantic Rainforests (Morais et al, 1995; Pimenta et al, 2009; Barbosa et al, 2016) as well as from crops of several Drosophila species (see Da Cunha, Shehata & De Oliveira, 1957; Morais et al, 1992; Morais, Pagnocca & Rosa, 2006; Batista et al, 2016). Species such as D. paraguayensis (see Batista et al, 2016) and D. maculifrons (see Da Cunha, Shehata & De Oliveira, 1957), which belong to D. tripunctata and D. guarani groups respectively, both of the Drosophila subgenus, had S. cerevisiae isolated from their crops.…”
Section: Discussionmentioning
confidence: 99%
“…Pimenta et al (2009) states that Drosophila may be a major vector of yeasts in Atlantic Rainforest. Our data shows that species of D. tripunctata and D. guarani groups are preferentially attracted to S. cerevisiae , reflecting their natural association in the wild; while species of subgenus Sophophora such as D. melanogaster , which is preferentially attracted to baits with H. uvarum may be naturally associated with apiculate yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological abilities and species composition of D. fasciola yeast communities differed from those of other forest‐inhabiting Drosophila , and the narrow feeding niches of these flies suggested the use of only part of the substrates available to the flies as food in the forest environment. Pimenta et al (2009) studied the yeast communities associated with fruits, mushrooms, tree exudates, and flies of the genus Drosophila , in two Atlantic Rain Forest fragments. A total of 608 yeast isolates were obtained, belonging to 71 species.…”
Section: Yeast Diversity In Tropical Forests and Related Forest Biome...mentioning
confidence: 99%